The effectiveness of the “Donante de Vida”Educational Program to improve knowledge and attitudes towards organ donation in students of a Confessional Private University - Mamani Limachi, Rut Ester (2017)
Organ donation is considered a very important and emerging issue in our society since there are a large number of people waiting for the donation of an organ or tissue, and if this is not resolved, the lack will continue. This study aimed to determine the effectiveness of the "Donante de Vida" educational program to improve knowledge and attitudes about organ donation. It was carried out with students of the first year of nursing of a Private Confessional University. It was quantitative with pre-experimental design,applying a pre and post-test, using as a tool a questionnaire of knowledge with 14 questions and 21 propositions. The intervention given to nursing students consists of three modules of education applied in 24 sessions developed in three months to a population of 39 students. The results showed effectiveness in the application of the educational program; in the pre-test, 97.4% of the students had a deficient level of knowledge and a predominantly indifferent attitude of 54.4%; after the intervention, the knowledge increased to 82.1% of a high level and an attitude of acceptance of 76.9%.